Pengurapan dalam Kitab-Kitab Sejarah Perjanjian Lama - Wassar, Sarah; Jaminter Ompusuggu; Joshua Christian Wenas; Tri Subekti; Yeyen Darmadi (Sekolah Tinggi Teologia Kerusso Indonesia, 2021)
When Jesus appeared to the disciples, he said: